2002
DOI: 10.1017/s0007125000161872
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the brain of a psychological treatment: Cognitive remediation therapy

Abstract: This is the first time that brain activation changes in a seriously disabled group of patients with schizophrenia can be associated clearly with psychological rather than pharmacological therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
1
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(104 citation statements)
references
References 23 publications
3
95
1
5
Order By: Relevance
“…Similar to other neuropsychiatric functions, there is not much information on the effectiveness of cognitive-behavioral therapy in the improvement of cognitive flexibility, and all relevant studies are into specific phobias and schizophrenia. In the current study blood flow and metabolism in anteriorlateral parts, which are both involved in cognitive flexibility, were improved during psychotherapy [31][32][33]. However, this is inconsistent with previous research, which is due to the differences in samples, damaging effect of substance abuse on brain structure, and therapy techniques.…”
Section: Discussioncontrasting
confidence: 96%
“…Similar to other neuropsychiatric functions, there is not much information on the effectiveness of cognitive-behavioral therapy in the improvement of cognitive flexibility, and all relevant studies are into specific phobias and schizophrenia. In the current study blood flow and metabolism in anteriorlateral parts, which are both involved in cognitive flexibility, were improved during psychotherapy [31][32][33]. However, this is inconsistent with previous research, which is due to the differences in samples, damaging effect of substance abuse on brain structure, and therapy techniques.…”
Section: Discussioncontrasting
confidence: 96%
“…This work expanded on previous research showing fMRI changes following cognitive training (Wexler et al, 2000;Wykes et al, 2002) by introducing group-level analysis and showing stimulus-general yet training-specific effects. The anterior cingulate and dorsal/dorsolateral prefrontal cortices are involved in working memory maintenance and cognitive control processes and have reduced activity in patients with schizophrenia (Barch et al, 2002;Carter et al, 2001;MacDonald et al, 2000).…”
Section: Discussionmentioning
confidence: 80%
“…Wexler et al (2000) presented preliminary evidence for a patient who showed normalization of function in the left inferior frontal cortex, a region of the brain involved in cognitive functions addressed by that training. Increases in activation in frontal and visual areas were also found in a subset of patients who showed the greatest behavioral improvement (Wykes et al, 2002). While these studies led the way in showing the possibility of concomitant changes in brain activity with training, they could not rule-out the possibility that they occurred only in selected patients, or that they reflected increased motivation or allegiance effects (increased desire to comply with task demands to assist in the experiment) as no active control groups were considered.…”
Section: Introductionmentioning
confidence: 82%
“…For example, using fMRI, Wykes et al (2002) demonstrated that individuals with schizophrenia who completed cognitive remediation therapy showed increased activation in the frontocortical region associated with working memory. Biological measures of neurocognition may also prove useful as short-or intermediate-term outcome variables if they are found to be linked to ecologically important aspects of functioning.…”
Section: Cognitive Measuresmentioning
confidence: 99%